2018
DOI: 10.1128/aem.00537-18
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance, Virulence Factors, and Genetic Profiles of Vibrio parahaemolyticus from Seafood

Abstract: is a widespread bacterium in the marine environment and is responsible for gastroenteritis in humans. Foodborne infections are mainly associated with the consumption of contaminated raw or undercooked fish and shellfish. The aim of this study was to determine the antimicrobial resistance, virulence factors, and genetic profiles of isolates from seafood originating from different countries. A total of 104 (17.5%) isolates were recovered from 595 analyzed samples. The isolates were tested for the presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
42
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 37 publications
16
42
1
1
Order By: Relevance
“…Though considered a "gold standard", it is only recently that PFGE has been extensively employed for subtyping environmental strains of V. parahaemolyticus [8,42,43]. The PFGE pattern of the 15 isolates of this study showed considerable diversity and the new serovars having pandemic attributes were not related to the pandemic O3:K6 isolate.…”
Section: Discussionmentioning
confidence: 65%
“…Though considered a "gold standard", it is only recently that PFGE has been extensively employed for subtyping environmental strains of V. parahaemolyticus [8,42,43]. The PFGE pattern of the 15 isolates of this study showed considerable diversity and the new serovars having pandemic attributes were not related to the pandemic O3:K6 isolate.…”
Section: Discussionmentioning
confidence: 65%
“…Yang et al (2017) isolated 98 V. parahaemolyticus strains from 504 seafood samples in 11 provinces of China and found that 68.38% of the isolates showed MDR phenotypes. Recently, Lopatek et al (2018) reported that 55.8% of the V. parahaemolyticus isolates (n = 104) recovered from 595 samples collected from Denmark, France, Germany, Italy, the Netherlands, Norway, Poland, Spain, Sri Lanka, and Turkey had resistance to ampicillin and streptomycin and one isolate resistant to ampicillin, streptomycin, and ciprofloxacin. Therefore, identification of virulence and resistance-associated factors in V. parahaemolyticus is imperative for food safety systems, particularly in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies shown that serotypes other than the O3:K6 pandemic clone also contain strong virulence genes [6]. For example, some non-pandemic clone strains of VP also had a single tdh without a toxRS, or some the strains contained thermostable related hemolysin (trh) and urease (ure) [7]. V. parahaemolyticus containing these genes could also cause cholera-like food poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…V. parahaemolyticus containing these genes could also cause cholera-like food poisoning. Thermolabile hemolysin gene (tlh) was generally considered to be non-pathogenic, but there were experiments [7]. It was indicated that raw seafood infected with VP containing the tlh could also cause diarrhea and blood in the stool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation